(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article examines the history of studying the Divan of Munis Khorezmi and provides a historical-etymological analysis of its language. The study discusses the composition of the divan, manuscript sources, linguistic features, and the origin and semantic development of lexical units belonging to Turkic, Arabic, and Persian layers. Particular attention is paid to the role of Munis’s poetry in the development of the Old Uzbek literary language and its significance as a historical linguistic source. The research demonstrates that the Divan of Munis is not only a literary masterpiece but also an important source for investigating the historical development of the Uzbek language.